A unique CD8+ T lymphocyte signature in pediatric type 1 diabetes. (September 2016) - Hamel, Yamina; Mauvais, François-Xavier; Pham, Hang-Phuong; Kratzer, Roland; Marchi, Christophe; Barilleau, Émilie; Waeckel-Enée, Emmanuelle; Arnoux, Jean-Baptiste; Hartemann, Agnès; Cordier, Corinne; Mégret, Jerome; Rocha, Benedita; et al.
Abstract: Human type 1 diabetes results from a destructive auto-reactive immune response in which CD8 + T lymphocytes play a critical role. Given the intense ongoing efforts to develop immune intervention to prevent and/or cure the disease, biomarkers suitable for prediction of disease risk and progress, as well as for monitoring of immunotherapy are required. We undertook separate multi-parameter analyses of single naïve and activated/memory CD8 + T lymphocytes from pediatric and adult patients, with the objective of identifying cellular profiles associated with onset of type 1 diabetes. We observe global perturbations in gene and protein expression and in the abundance of T cell populations characterizing pediatric but not adult patients, relative to age-matched healthy individuals. Pediatric diabetes is associated with a unique population of CD8 + T lymphocytes co-expressing effector (perforin, granzyme B) and regulatory (transforming growth factor β, interleukin-10 receptor) molecules. This population persists after metabolic normalization and is especially abundant in children with high titers of auto-antibodies to glutamic acid decarboxylase and with elevated HbA1c values. These findings highlight striking differences between pediatric and adult type 1 diabetes, indicate prolonged large-scale perturbations in the CD8 + T cell compartment in the former, and suggest that CD8 + CD45RA − T cells co-expressing effector and regulatory factors are of interest as biomarkers in pediatric type 1 diabetes. Highlights: Onset of pediatric but not adult type 1 diabetes is associated with a specific signature in bulk CD8 + T lymphocytes. This signature is detected in single CD8 + T cells both at the level of gene and protein expression. Pediatric signature CD8 + T cells co-express perforin and TGF-β. Signature CD8 + T cells persist after metabolic normalization. Signature correlation with GAD autoantibody titers and HbA1c levels suggest a role in diabetes pathogenesis.